Festival Ritual On The 40th Day Of Death (Socio-Cultural Analysis In Gampong Geudong, Sungai Mas District, West Aceh Regency) (Jurnal Adabiya, 2025)
Kenduri on the 40th day of death is a tradition carried out by the Acehnese people as part of a series of ceremonies to commemorate someone's death on the 40th day after death which functions as a significant socio-cultural event that reflects the values and beliefs of the community around death and memory. This article aims to describe in depth the process of the kenduri ritual on the 40th day of death, the meaning and symbols of its implementation and the community's perception of the kenduri on the 40th day of death in Gampong Geudong, Sungai Mas District, West Aceh Regency. This study uses a qualitative research method with an ethnographic approach. Data collection techniques use observation, interviews and documentation studies. The results of the study show that the 40-day kenduri is usually held at the funeral home around 40 days after death, as a continuation of the series of death ceremonies that begin from sakaratul maut until the 100th night. Before the peak event, a village meeting is usually held and notification is given to all residents and relatives so that they can attend and participate in the gathering to hold a prayer together. Preparation for the feast includes making cakes that have strong symbolic and social meanings such as Bu Leukat (symbolizing attachment) and Breuh/Umping (additional food for the spirit) which are manifested through the implementation of the feast and the giving of Kue Toeng Peut Ploh, as a form of respect and prayer for the spirit and to bind social relations in the community. The community also views the 40-day death feast as a very important and sacred cultural tradition, which is still believed to exist from generation to generation and as a form of solidarity and social concern between village residents.